Demonstration - excerpts from recombinant DNA videos - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1994)
Demonstration and experiments of agarose gel electrophoresis. The oulines are : preapare agarose gel, electrophoresis, stain DNA and analyze.
Copy available in DVD format
Keywords: Recombinant DNA; DNA